Program Kelas Eksklusif Calistung Sebagai Upaya Peningkatan Literasi Dan Numerasi Di SD Negeri Medokan Semampir 1 Surabaya - Fatimatus Zahro; Dewi Ayu Puspitasari; Ridha Hastika (Pusat Riset dan Inovasi Nasional, 2024)
One of the programmes of Merdeka Belajar Kampus Merdeka (MBKM) is Kampus Mengajar Program. The program aims to help schools that have C accreditation as well as schools that are leading, remote, and lagging behind. (3t). Through campus education, students can become agents of change and work with teachers to help improve education in Indonesia. SD Negeri Medokan Semampir 1 Surabaya is one of the schools involved in this program. During the assignment, students design work programmes to meet school needs and help improve literacy, numeration, and technology adaptation. To help students who do not have the ability to count, write, and read. Kelas Eksklusif Calistung is the program we designed. In these activities, qualitative descriptive approaches are used, with data collection through observations, interviews, and documentation. The results of the activities show that the Kelas Eksklusif Calistung program at SD Negeri Medokan Semampir 1 Surabaya runs well and provides positive benefits to all students, especially the targeted students.